Volcanically-Induced Environmental and Floral Changes Across the Triassic-Jurassic (T-J) Transition - Zhang, Peixin; Lu, Jing; Yang, Minfang; Bond, David P. G.; Greene, Sarah E.; Liu, Le; Zhang, Yuanfu; Wang, Ye; Wang, Ziwei; Li, Shan; Shao, Longyi; Hilton, Jason (Frontiers in Ecology and Evolution, 2022)
The End-Triassic Mass Extinction (ETME) saw the catastrophic loss of ca. 50% of marine genera temporally associated with emplacement of the Central Atlantic Magmatic Province (CAMP). However, the effects of the ETME on land is a controversial topic. Evaluation of the disparate cause(s) and effects of the extinction requires additional, detailed terrestrial records of these events. Here, we present a multidisciplinary record of volcanism and environmental change from an expanded Triassic-Jurassic (T-J) transition preserved in lacustrine sediments from the Jiyuan Basin, North China. High-resolution chemostratigraphy, palynological, kerogen, and sedimentological data reveal that terrestrial conditions responded to and were defined by large-scale volcanism. The record of sedimentary mercury reveals two discrete CAMP eruptive phases during the T-J transition. Each of these can be correlated with large, negative C isotope excursions (CIE-I of −4.7‰; CIE-II of −2.9‰), significantly reduced plant diversity (with ca. 45 and 44% generic losses, respectively), enhanced wildfire (marked by increased fusinite or charcoal content), and major climatic shifts toward drier and hotter conditions (indicated by the occurrence of calcareous nodules, increased Classopollis pollen content, and PCA analysis). Our results show that CAMP eruptions may have followed a bimodal eruptive model and demonstrate the powerful ability of large-scale volcanism to alter the global C cycle and profoundly affect the climate, in turn leading to enhanced wildfires and a collapse in land plant diversity during the T-J transition.